Composite current collector

By depositing a transition layer, a metal layer and a protective layer on the base film of the composite fluid collector, and modifying the base film with thermally expanded microspheres, the problem of the composite fluid collector being prone to failure under high temperature or electrochemical action is solved, and the performance of the battery is significantly improved.

CN119650709APending Publication Date: 2025-03-18JIANGYIN NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411671740.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Existing composite liquid collectors are prone to failures such as cracking, layering, wrinkling and shedding under high temperature environment or electrochemical action, affecting the electrochemical and safety performance of the battery.

Method used

By uniformly mixing the thermally expanded microspheres with the polymer material, melt extrusion and bidirectionally stretching, a composite fluid with a modified base film was prepared. The composite fluid collector deposits a transition layer, a metal layer and a protective layer on the base film to improve the stability and adhesion of the base film.

Benefits of technology

It effectively avoids interlayer defects, cracking, and stratification during production and use of composite liquids, and improves the electrochemical and safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of composite current collectors, and discloses a composite current collector. Comprising the following operation steps: S1, uniformly mixing thermal expansion microspheres and a polymer material, and performing melt extrusion and two-way stretching to obtain a current collector base film; s2, depositing a transition layer on each of the two surfaces of the current collector base film to obtain a composite collector film A; s3, depositing a metal layer on each of the two surfaces of the transition layer of the composite film A to obtain a composite film B; and S4, depositing a protective layer on each of the two surfaces of the metal layer of the composite film B to obtain the composite current collector.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite current collectors, in particular to a composite current collector. Background Art

[0002] At present, composite current collectors based on polymer membranes have received extensive attention and application in the new energy industry. The preparation of the composite current collector usually uses the physical vapor deposition (PVD) method to deposit a layer of metal on a polymer film (such as polyester, polyolefin, etc.) to prepare a composite current collector with good conductivity. Compared with traditional current collectors, composite current collectors based on polymer membranes have the characteristics of low cost, light weight, and good internal insulation. These characteristics enable the composite current collector to reduce the cost of the battery and improve the energy density and safety of the battery when used in the battery.

[0003] In the process of producing composite current collectors using common technologies and processes, the base film is easily shrunk by heat, making it impossible for the metal layer to be closely arranged on the base film. In particular, local uneven heating will cause the current collector to fail easily, such as cracking, delamination, wrinkling and falling off. In actual use, if it is in a high temperature environment or under electrochemical action, the defects are more serious, which will have a great impact on the electrochemical performance and safety performance of the battery based on this composite current collector. Summary of the invention

[0004] The object of the present invention is to provide a composite current collector to solve the problems raised in the prior art.

[0005] To achieve the above object, the present invention provides the following technical solutions: A composite current collector comprises the following steps: S1: uniformly mixing the heat-expandable microspheres and the polymer material, melt-extruding, and biaxially stretching to obtain a current collector base film; S2: depositing a transition layer on both sides of the current collector base film to obtain a composite current collector film A; S3: depositing another metal layer on both sides of the transition layer of the composite film A to obtain a composite film B; S4: depositing another protective layer on both sides of the metal layer of the composite film B to obtain a composite current collector.

[0006] More optimally, the current collector base film includes 5wt%~5wt% of heat-expandable microspheres and 95wt%~99.5wt% of polymer materials; the particle size of the heat-expandable microspheres is 5μm~20μm; the biaxial stretching includes longitudinal stretching and transverse stretching, and its process conditions are: the longitudinal stretching ratio is (3~6):1, the longitudinal stretching temperature is 80~110℃, the transverse stretching ratio is (2~4):1, and the transverse stretching temperature is 80~110℃.

[0007] In the scheme, heat-expandable microspheres are used as fillers, and their content is preferably 0.1wt%~10wt%, and more preferably 0.5wt%~5wt%. Too few heat-expandable microspheres will have no effect, and too many heat-expandable microspheres will cause excessive and uneven pores in the base film. The expansion range and size are to be determined according to different base films.

[0008] More optimally, the metal layer on any side of the current collector base film is one layer or more layers, the thickness of each layer is 50nm~1200nm, and the total thickness of the metal layer on any side of the current collector base film is 500nm~2000nm; the thickness of the protective layer is 20nm~80nm; the thickness of the current collector base film is 1.0μm~10μm; the thickness of the composite current collector is 3~20μm.

[0009] In the scheme, the current collector base film is prepared by melt-extrusion-biaxial stretching method. Considering the application requirements of the composite current collector and the difficulty and cost of the preparation process, the preferred thickness is 1.0-10 μm; the thickness of the protective layer is between 10 nm and 100 nm, and the preferred thickness is 20 nm to 80 nm; the thickness of the protective layer shall not exceed one tenth of the thickness of the metal layer; The transition layer can enhance the bonding force between the current collector base film and the metal layer; wherein, the bonding force between the transition layer and the metal layer will affect the relative movement between the metal layer and the current collector base film during the deformation of the composite current collector, thereby affecting the deformation and fission behavior of the transition layer, and further affecting its effect on improving the safety performance of the battery; the bonding force between the transition layer and the metal layer is 100N / m~900N / m.

[0010] Preferably, the polymer material includes one or more of polyethylene terephthalate, polypropylene, polybutylene terephthalate, polyethylene naphthalate, polyethylene, polypropylene, polyvinyl chloride, polyvinylidene fluoride, polytetrafluoroethylene, polyphenylene sulfide, polyphenylene oxide, polystyrene, and polyimide; The raw material of the transition layer includes one or more of aluminum oxide, silicon oxide, titanium oxide, nickel, chromium, titanium, nickel-chromium alloy, nickel-chromium-copper alloy, and silicon-aluminum alloy; The raw material of the metal layer includes one or more of aluminum, copper, gold, silver, nickel and zinc and alloys thereof; The material of the protective layer includes one or more of nickel, chromium, nickel-chromium alloy, nickel-based alloy, copper-based alloy, copper oxide, aluminum oxide, nickel oxide, chromium oxide, cobalt oxide, copper-chromium oxide, graphite, carbon black, carbon nano-quantum dots, carbon nanotubes, carbon nanofibers, graphene and graphene oxide.

[0011] In the scheme, the metal layer provides conductivity for the composite current collector; wherein, if the metal layer is too thin, the conductivity is poor; if the metal layer is too thick, the prepared composite current collector is too thick and heavy, which is not conducive to improving the energy density of the battery; in the present invention, considering the conductivity and the improvement of energy density, the preferred total thickness is 800nm~1200nm; In the solution, the material of the protective layer can be two layers, the materials of the two layers can be consistent or inconsistent, and the thickness can be consistent or inconsistent; the protective layer can prevent the metal layer from being chemically corroded or physically damaged.

[0012] More optimally, the deposition method of the metal layer includes one or more of evaporation, magnetron sputtering, chemical plating, electroplating, and chemical vapor deposition; the deposition method of the protective layer includes one or more of physical vapor deposition, chemical vapor deposition, in-situ forming, and coating.

[0013] Preferably, the deposition method of the metal layer is electroplating or magnetron sputtering, and the specific process is as follows: The electroplating conditions are as follows: the anode is a high-purity metal with a purity of ≥99.9%, the cathode is a titanium plate; the current intensity is between 20000A and 50000A, and the current density is 5000A / m 2 ~10000A / m 2 ; The copper ion concentration is generally controlled at 65g / L~100g / L, H 2 SO 4 The concentration is 180g / L~220g / L; The magnetron sputtering conditions are as follows: using high-purity metal as the target material with a purity of ≥99.9%, the target power supply is a DC power supply with a power of 2kW~20kW, the vacuum degree is ≤0.1Pa, the gas source is argon, the argon flow rate is 20mL / min~500mL / min, and each coating time is 0.1s~120s.

[0014] The more optimized preparation method of the heat-expandable microspheres is as follows: (1) polyvinyl pyrrolidone, sodium dodecyl sulfate, modified ferrosoferric oxide, sodium chloride, and deionized water are uniformly mixed to obtain a water phase for use; acrylonitrile, methyl methacrylate, methyl acrylate, N,N-dimethylacrylamide, trimethylolpropane trimethacrylate, isopentane, butadiene, and dilauroyl peroxide are uniformly mixed to obtain an oil phase for use; (2) the pressure is set to 1MPa~1.2MPa, the water phase and the oil phase are mixed at room temperature for 15~20 minutes at a speed of 5000rpm~8000rpm, the temperature is raised to 40℃~60℃, the reaction is carried out for 18~22 hours, the mixture is cooled to room temperature, filtered, washed, and dried to obtain heat-expandable microspheres.

[0015] More optimally, the raw materials of the water phase include the following components: 80-100 parts of deionized water, 30-40 parts of sodium chloride, 15-20 parts of polyvinyl pyrrolidone, 4-5 parts of sodium dodecyl sulfate, and 5-7 parts of modified ferrosoferric oxide, by mass; the raw materials of the oil phase include the following components: 50-60 parts of methyl acrylate, 30-35 parts of acrylonitrile, 25-35 parts of isopentane, 6-8 parts of methyl methacrylate, 3-5 parts of N,N-dimethylacrylamide, 5-8 parts of butadiene, 3-5 parts of trimethylolpropane trimethacrylate, and 1-3 parts of dilauroyl peroxide.

[0016] In the scheme, polyvinyl pyrrolidone is used as a dispersant to increase the viscosity of the mixture and help form a uniform aqueous phase; sodium dodecyl sulfate is used as an additive to form a suspended stable system through a violent homogenization process; sodium chloride can effectively reduce the solubility of the polymerizable monomer in the aqueous phase.

[0017] In the scheme, acrylonitrile provides cyano groups, which makes the polymer have excellent thermal stability and mechanical strength and strengthens the structure of the microspheres; the addition of methyl acrylate can improve the thermal expansion properties of the microspheres, so that they can expand better when heated, thereby improving the insulation and shock absorption properties of the material; the polymerization reaction of methyl acrylate can affect the foaming process of the microspheres, thereby adjusting their density and porosity; methyl methacrylate can increase the transparency and rigidity of the polymer, improve the surface properties and weather resistance of the microspheres, and provide acidic functional groups to enhance the reactivity and compatibility of the polymer, making the microspheres more adaptable and functional; the addition of butadiene can improve the toughness and elasticity of the heat-expandable microspheres; N,N-dimethylacrylamide exhibits thermoplasticity when heated, can soften and expand at a certain temperature, so that the gas is easier to be enclosed inside the microspheres, and it is well compatible with other polymers or additives, which helps to form a uniform foaming system, prevent phase separation, and enhance the foaming effect; trimethylolpropane trimethacrylate is used as a crosslinking agent to increase the network structure of the polymer and improve its strength and stability; isopentane is used as a foaming agent and dilauroyl peroxide is used as an initiator.

[0018] The preparation method of the modified ferrosoferric oxide is as follows: (1) adding ferric chloride to a mixed solution of propylene glycol and deionized water, mixing uniformly, adding cysteine, reacting at 0.2 MPa to 0.3 MPa and 180°C to 210°C for 5 to 6 hours, cooling to room temperature, washing, and drying to obtain thiolated ferrosoferric oxide; (2) ultrasonically dispersing thiolated ferrosoferric oxide in tetrahydrofuran, adding methacrylamide, (5-(pent-4-en-1-yloxy)pyridin-3-yl)boric acid, and azobisisobutyronitrile, and irradiating at an emission wavelength of 365 nm and a light intensity of 90 mW / cm 2 ~100mW / cm 2Irradiate under ultraviolet light for 2 to 3 hours to obtain modified ferrosoferric oxide.

[0019] More optimally, the raw materials of the thiolated ferrosoferric oxide include the following components: by mass, 0.6-0.8 parts of ferric chloride, 5-10 parts of propylene glycol, 5-10 parts of deionized water, and 1.5-2.2 parts of cysteine; the raw materials of the modified ferrosoferric oxide include the following components: by mass, 0.5-1 parts of thiolated ferrosoferric oxide, 3-4 parts of methacrylamide, 1-2 parts of (5-(pent-4-en-1-yloxy)pyridin-3-yl)boric acid, 0.002-0.0025 parts of azobisisobutyronitrile, and 20-25 parts of tetrahydrofuran.

[0020] In the scheme, the thiol group on the thiolated ferrosoferric oxide is reacted with methacrylamide and the vinyl group on (5-(pent-4-en-1-yloxy)pyridin-3-yl)boric acid through a click chemistry reaction to obtain modified ferrosoferric oxide; the introduction of ferrosoferric oxide can improve the strength and stability of the microspheres, allowing them to maintain their shape during thermal expansion, and help regulate the battery temperature to prevent overheating; these monomers form a uniform network structure during the polymerization process, which helps the microspheres achieve better expansion when heated; the pyridine group on (5-(pent-4-en-1-yloxy)pyridin-3-yl)boric acid can form hydrogen bonds or coordination effects with the surface or other components of the microspheres, thereby enhancing the stability and structural integrity of the microspheres.

[0021] Compared with the prior art, the present invention has the following beneficial effects: The invention adds a certain amount of expanded microspheres to a polymer material for modification through melt extrusion to obtain a current collector base film. During the melting process, the gas pressure in the expanded microspheres increases and the thermoplastic shell softens, thereby significantly increasing the volume of the expanded microspheres. After cooling, the shell of the expanded microspheres hardens again and the volume is fixed, thereby reducing the density and improving the surface structure, improving the stability of the base film, and avoiding interlayer defects, cracking, stratification and the like during the production and use of the composite current collector.

[0022] Secondly, the heat-expandable microspheres have good elasticity. The expanded microspheres are easily compressed and return to their original volume when the pressure is released. Therefore, when the microspheres are subjected to local heat and sudden mechanical impact pressure, they absorb part of the energy and protect the composite current collector. At the same time, the special air-filled closed-cell structure of the expanded microspheres makes them have good thermal insulation and electrical insulation properties. After being added to the polymer as a filler, the thermal stability and insulation of the base film are improved, thereby ensuring the safety performance of the battery based on this composite current collector.

[0023] Therefore, the composite current collector with a modified base film prepared by the present invention is not prone to defects during production and use, so that the electrochemical performance and safety performance of the battery based on the new composite current collector are significantly improved.

[0024] The composite current collector with a modified base film prepared by this method is not prone to defects during production and use, so the electrochemical performance and safety performance of the battery based on the new composite current collector are significantly improved. DETAILED DESCRIPTION

[0025] The following will be combined with the parts by mass in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0026] The preparation method of modified ferrosoferric oxide is as follows: (1) adding 0.6-0.8 parts of ferric chloride to a mixed solution of 5 parts of propylene glycol and 5 parts of deionized water, uniformly mixing, adding 1.5 parts of cysteine, reacting at 0.2 MPa and 190°C for 5 hours, cooling to room temperature, washing, and drying to obtain thiolated ferrosoferric oxide; (2) ultrasonically dispersing 0.8 parts of thiolated ferrosoferric oxide in 25 parts of tetrahydrofuran, adding 5 parts of methacrylamide and 0.002 parts of azobisisobutyronitrile, and irradiating at an emission wavelength of 365 nm and a light intensity of 100 mW / cm 2 The product was irradiated under ultraviolet light for 2 hours to obtain modified ferrosoferric oxide.

[0027] The preparation method of heat-expandable microspheres is as follows: (1) 15 parts of polyvinyl pyrrolidone, 4 parts of sodium dodecyl sulfate, 7 parts of modified ferrosoferric oxide, 40 parts of sodium chloride, and 100 parts of deionized water are uniformly mixed to obtain a water phase for later use; 35 parts of acrylonitrile, 7 parts of methyl methacrylate, 50 parts of methyl acrylate, 5 parts of N,N-dimethylacrylamide, 4 parts of trimethylolpropane trimethacrylate, 30 parts of isopentane, 6 parts of butadiene, and 2 parts of dilauroyl peroxide are uniformly mixed to obtain an oil phase for later use; (2) the pressure is set to 1 MPa, the water phase and the oil phase are mixed at room temperature for 15 minutes at a speed of 7000 rpm, the temperature is raised to 60°C, the reaction is carried out for 22 hours, the mixture is cooled to room temperature, filtered, washed, and dried to obtain heat-expandable microspheres.

[0028] Example 1: The preparation of a composite current collector comprises the following steps: S1: 0.5 wt% heat-expandable microspheres (average diameter 5 μm) were uniformly mixed with 99.5 wt% polypropylene, melted at 200 °C for 30 minutes, extruded, and biaxially stretched to obtain a 4.5 μm current collector base film; The process conditions of biaxial stretching are as follows: the longitudinal stretching ratio is 5:1, the longitudinal stretching temperature is 90°C, the transverse stretching ratio is 3:1, and the transverse stretching temperature is 90°C; S2: A 5 nm thick transition layer was deposited on each side of the current collector base film using a nickel-chromium alloy target (purity: 99.99%) as the target material by magnetron sputtering (power 4.0 kW, argon gas flow rate 50 mL / min, coating vacuum degree 0.08 Pa, coating time 1 s, main roller temperature during coating process 10°C) to obtain a composite current collector film A; S3: A 900 nm thick metal layer was deposited on both sides of the transition layer of the composite film A using a copper target (purity: 99.99%) as the target material by magnetron sputtering (power of 12.0 kW, argon flow of 70 mL / min, coating vacuum of 0.1 Pa, coating time of 100 s, cooling temperature of the main roller during the coating process of -5 °C) to obtain a composite film B; S4: The composite membrane B is immersed in a 0.5 g / L chromic anhydride aqueous solution at 25°C until the protective layer thickness is 50 nm, then washed in a pure water tank, and dried in an oven at 60°C to obtain a composite current collector with a total thickness of 6.41 μm.

[0029] Example 2 is based on Example 1, the heat-expandable microspheres are 1wt% and the polypropylene is 99wt%; comprising the following steps: S1: 1wt% heat-expandable microspheres (average diameter 5μm) were uniformly mixed with 99wt% polypropylene, melted at 200℃ for 30 minutes, extruded, and biaxially stretched to obtain a 4.5μm current collector base film; The process conditions of biaxial stretching are as follows: the longitudinal stretching ratio is 5:1, the longitudinal stretching temperature is 90°C, the transverse stretching ratio is 3:1, and the transverse stretching temperature is 90°C; S2: A 5 nm thick transition layer was deposited on each side of the current collector base film using a nickel-chromium alloy target (purity: 99.99%) as the target material by magnetron sputtering (power 4.0 kW, argon gas flow rate 50 mL / min, coating vacuum degree 0.08 Pa, coating time 1 s, main roller temperature during coating process 10°C) to obtain a composite current collector film A; S3: A 900 nm thick metal layer was deposited on both sides of the transition layer of the composite film A using a copper target (purity: 99.99%) as the target material by magnetron sputtering (power of 12.0 kW, argon flow of 70 mL / min, coating vacuum of 0.1 Pa, coating time of 100 s, cooling temperature of the main roller during the coating process of -5 °C) to obtain a composite film B; S4: The composite membrane B is immersed in a 0.5 g / L chromic anhydride aqueous solution at 25°C until the protective layer thickness is 50 nm, then washed in a pure water tank, and dried in an oven at 60°C to obtain a composite current collector with a total thickness of 6.41 μm.

[0030] Example 3 is based on Example 1, the heat-expandable microspheres are 2.5wt% and the polypropylene is 97.5wt%; comprising the following steps: S1: 2.5wt% heat-expandable microspheres (average diameter 5μm) were uniformly mixed with 97.5wt% polypropylene, melted at 200℃ for 30 minutes, extruded, and biaxially stretched to obtain a 4.5μm current collector base film; The process conditions of biaxial stretching are as follows: the longitudinal stretching ratio is 5:1, the longitudinal stretching temperature is 90°C, the transverse stretching ratio is 3:1, and the transverse stretching temperature is 90°C; S2: A 5 nm thick transition layer was deposited on each side of the current collector base film using a nickel-chromium alloy target (purity: 99.99%) as the target material by magnetron sputtering (power 4.0 kW, argon gas flow rate 50 mL / min, coating vacuum degree 0.08 Pa, coating time 1 s, main roller temperature during coating process 10°C) to obtain a composite current collector film A; S3: A 900 nm thick metal layer was deposited on both sides of the transition layer of the composite film A using a copper target (purity: 99.99%) as the target material by magnetron sputtering (power of 12.0 kW, argon flow of 70 mL / min, coating vacuum of 0.1 Pa, coating time of 100 s, cooling temperature of the main roller during the coating process of -5 °C) to obtain a composite film B; S4: The composite membrane B is immersed in a 0.5 g / L chromic anhydride aqueous solution at 25° C. until the protective layer thickness is 50 nm, then washed in a pure water tank, and dried in an oven at 60° C. to obtain a composite current collector.

[0031] Example 4 is based on Example 1, the heat-expandable microspheres are 5wt% and the polypropylene is 95wt%; comprising the following steps: S1: 5 wt% heat-expandable microspheres (average diameter 5 μm) were uniformly mixed with 95 wt% polypropylene, melted at 200 °C for 30 minutes, extruded, and biaxially stretched to obtain a 4.5 μm current collector base film; The process conditions of biaxial stretching are as follows: the longitudinal stretching ratio is 5:1, the longitudinal stretching temperature is 90°C, the transverse stretching ratio is 3:1, and the transverse stretching temperature is 90°C; S2: A 5 nm thick transition layer was deposited on each side of the current collector base film using a nickel-chromium alloy target (purity: 99.99%) as the target material by magnetron sputtering (power 4.0 kW, argon gas flow rate 50 mL / min, coating vacuum degree 0.08 Pa, coating time 1 s, main roller temperature during coating process 10°C) to obtain a composite current collector film A; S3: A 900 nm thick metal layer was deposited on both sides of the transition layer of the composite film A using a copper target (purity: 99.99%) as the target material by magnetron sputtering (power of 12.0 kW, argon flow of 70 mL / min, coating vacuum of 0.1 Pa, coating time of 100 s, cooling temperature of the main roller during the coating process of -5 °C) to obtain a composite film B; S4: The composite membrane B is immersed in a 0.5 g / L chromic anhydride aqueous solution at 25°C until the protective layer thickness is 50 nm, then washed in a pure water tank, and dried in an oven at 60°C to obtain a composite current collector with a total thickness of 6.41 μm.

[0032] Example 5 is based on Example 1, the heat-expandable microspheres are 0.1wt% and the polypropylene is 99.9wt%; comprising the following steps: S1: 0.1wt% heat-expandable microspheres (average diameter 5μm) were uniformly mixed with 99.9wt% polypropylene, melted at 200℃ for 30 minutes, extruded, and biaxially stretched to obtain a 4.5μm current collector base film; The process conditions of biaxial stretching are as follows: the longitudinal stretching ratio is 5:1, the longitudinal stretching temperature is 90°C, the transverse stretching ratio is 3:1, and the transverse stretching temperature is 90°C; S2: A 5 nm thick transition layer was deposited on each side of the current collector base film using a nickel-chromium alloy target (purity: 99.99%) as the target material by magnetron sputtering (power 4.0 kW, argon gas flow rate 50 mL / min, coating vacuum degree 0.08 Pa, coating time 1 s, main roller temperature during coating process 10°C) to obtain a composite current collector film A; S3: A 900 nm thick metal layer was deposited on both sides of the transition layer of the composite film A using a copper target (purity: 99.99%) as the target material by magnetron sputtering (power of 12.0 kW, argon flow of 70 mL / min, coating vacuum of 0.1 Pa, coating time of 100 s, cooling temperature of the main roller during the coating process of -5 °C) to obtain a composite film B; S4: The composite membrane B is immersed in a 0.5 g / L chromic anhydride aqueous solution at 25°C until the protective layer thickness is 50 nm, then washed in a pure water tank, and dried in an oven at 60°C to obtain a composite current collector with a total thickness of 6.41 μm.

[0033] Example 6 is based on Example 1, with the heat-expandable microspheres accounting for 10 wt% and the polypropylene accounting for 90 wt%; comprising the following steps: S1: 10 wt% heat-expandable microspheres (average diameter 5 μm) were uniformly mixed with 90 wt% polypropylene, melted at 200 °C for 30 minutes, extruded, and biaxially stretched to obtain a 4.5 μm current collector base film; The process conditions of biaxial stretching are as follows: the longitudinal stretching ratio is 5:1, the longitudinal stretching temperature is 90°C, the transverse stretching ratio is 3:1, and the transverse stretching temperature is 90°C; S2: A 5 nm thick transition layer was deposited on each side of the current collector base film using a nickel-chromium alloy target (purity: 99.99%) as the target material by magnetron sputtering (power 4.0 kW, argon gas flow rate 50 mL / min, coating vacuum degree 0.08 Pa, coating time 1 s, main roller temperature during coating process 10°C) to obtain a composite current collector film A; S3: A 900 nm thick metal layer was deposited on both sides of the transition layer of the composite film A using a copper target (purity: 99.99%) as the target material by magnetron sputtering (power of 12.0 kW, argon flow of 70 mL / min, coating vacuum of 0.1 Pa, coating time of 100 s, cooling temperature of the main roller during the coating process of -5 °C) to obtain a composite film B; S4: The composite membrane B is immersed in a 0.5 g / L chromic anhydride aqueous solution at 25°C until the protective layer thickness is 50 nm, then washed in a pure water tank, and dried in an oven at 60°C to obtain a composite current collector with a total thickness of 6.41 μm.

[0034] Example 7 is based on Example 3, the average diameter of the heat-expandable microspheres is 10 μm; comprising the following steps: S1: 2.5wt% heat-expandable microspheres (average diameter 10μm) were uniformly mixed with 97.5wt% polypropylene, melted at 200℃ for 30 minutes, extruded, and biaxially stretched to obtain a 4.5μm current collector base film; The process conditions of biaxial stretching are as follows: the longitudinal stretching ratio is 5:1, the longitudinal stretching temperature is 90°C, the transverse stretching ratio is 3:1, and the transverse stretching temperature is 90°C; S2: A 5 nm thick transition layer was deposited on each side of the current collector base film using a nickel-chromium alloy target (purity: 99.99%) as the target material by magnetron sputtering (power 4.0 kW, argon gas flow rate 50 mL / min, coating vacuum degree 0.08 Pa, coating time 1 s, main roller temperature during coating process 10°C) to obtain a composite current collector film A; S3: A 900 nm thick metal layer was deposited on both sides of the transition layer of the composite film A using a copper target (purity: 99.99%) as the target material by magnetron sputtering (power of 12.0 kW, argon flow of 70 mL / min, coating vacuum of 0.1 Pa, coating time of 100 s, cooling temperature of the main roller during the coating process of -5 °C) to obtain a composite film B; S4: The composite membrane B is immersed in a 0.5 g / L chromic anhydride aqueous solution at 25°C until the protective layer thickness is 50 nm, then washed in a pure water tank, and dried in an oven at 60°C to obtain a composite current collector with a total thickness of 6.41 μm.

[0035] Example 8 is based on Example 3, the average diameter of the heat-expandable microspheres is 20 μm; comprising the following steps: S1: 2.5wt% heat-expandable microspheres (average diameter 20μm) were uniformly mixed with 97.5wt% polypropylene, melted at 200℃ for 30 minutes, extruded, and biaxially stretched to obtain a 4.5μm current collector base film; The process conditions of biaxial stretching are as follows: the longitudinal stretching ratio is 5:1, the longitudinal stretching temperature is 90°C, the transverse stretching ratio is 3:1, and the transverse stretching temperature is 90°C; S2: A 5 nm thick transition layer was deposited on each side of the current collector base film using a nickel-chromium alloy target (purity: 99.99%) as the target material by magnetron sputtering (power 4.0 kW, argon gas flow rate 50 mL / min, coating vacuum degree 0.08 Pa, coating time 1 s, main roller temperature during coating process 10°C) to obtain a composite current collector film A; S3: A 900 nm thick metal layer was deposited on both sides of the transition layer of the composite film A using a copper target (purity: 99.99%) as the target material by magnetron sputtering (power of 12.0 kW, argon flow of 70 mL / min, coating vacuum of 0.1 Pa, coating time of 100 s, cooling temperature of the main roller during the coating process of -5 °C) to obtain a composite film B; S4: The composite membrane B is immersed in a 0.5 g / L chromic anhydride aqueous solution at 25°C until the protective layer thickness is 50 nm, then washed in a pure water tank, and dried in an oven at 60°C to obtain a composite current collector with a total thickness of 6.41 μm.

[0036] Example 9 is based on Example 3, the average diameter of the heat-expandable microspheres is 10 μm, and the melt extrusion temperature is 300° C.; comprising the following steps: S1: 2.5wt% heat-expandable microspheres (average diameter of 10μm) were uniformly mixed with 97.5wt% polypropylene, melted at 300℃ for 30 minutes, extruded, and biaxially stretched to obtain a 4.5μm current collector base film; The process conditions of biaxial stretching are as follows: the longitudinal stretching ratio is 5:1, the longitudinal stretching temperature is 90°C, the transverse stretching ratio is 3:1, and the transverse stretching temperature is 90°C; S2: A 5 nm thick transition layer was deposited on each side of the current collector base film using a nickel-chromium alloy target (purity: 99.99%) as the target material by magnetron sputtering (power 4.0 kW, argon gas flow rate 50 mL / min, coating vacuum degree 0.08 Pa, coating time 1 s, main roller temperature during coating process 10°C) to obtain a composite current collector film A; S3: A 900 nm thick metal layer was deposited on both sides of the transition layer of the composite film A using a copper target (purity: 99.99%) as the target material by magnetron sputtering (power of 12.0 kW, argon flow of 70 mL / min, coating vacuum of 0.1 Pa, coating time of 100 s, cooling temperature of the main roller during the coating process of -5 °C) to obtain a composite film B; S4: The composite membrane B is immersed in a 0.5 g / L chromic anhydride aqueous solution at 25°C until the protective layer thickness is 50 nm, then washed in a pure water tank, and dried in an oven at 60°C to obtain a composite current collector with a total thickness of 6.41 μm.

[0037] Comparative Example 1 is based on Example 1, but without adding heat-expandable microspheres; and comprises the following steps: S1: melt polypropylene at 200°C for 30 minutes, extrude and biaxially stretch to obtain a 4.5 μm current collector base film; The process conditions of biaxial stretching are as follows: the longitudinal stretching ratio is 5:1, the longitudinal stretching temperature is 90°C, the transverse stretching ratio is 3:1, and the transverse stretching temperature is 90°C; S2: A 5 nm thick transition layer was deposited on each side of the current collector base film using a nickel-chromium alloy target (purity: 99.99%) as the target material by magnetron sputtering (power 4.0 kW, argon gas flow rate 50 mL / min, coating vacuum degree 0.08 Pa, coating time 1 s, main roller temperature during coating process 10°C) to obtain a composite current collector film A; S3: A 900 nm thick metal layer was deposited on both sides of the transition layer of the composite film A using a copper target (purity: 99.99%) as the target material by magnetron sputtering (power of 12.0 kW, argon flow of 70 mL / min, coating vacuum of 0.1 Pa, coating time of 100 s, cooling temperature of the main roller during the coating process of -5 °C) to obtain a composite film B; S4: The composite membrane B is immersed in a 0.5 g / L chromic anhydride aqueous solution at 25°C until the protective layer thickness is 50 nm, then washed in a pure water tank, and dried in an oven at 60°C to obtain a composite current collector with a total thickness of 6.41 μm.

[0038] Comparative Example 2 is based on Example 1, except that heat-expandable microspheres are not added and polypropylene is replaced with polyethylene terephthalate; the method comprises the following steps: S1: polyethylene terephthalate was melted at 200°C for 30 minutes, extruded, and biaxially stretched to obtain a 4.5 μm current collector base film; The process conditions of biaxial stretching are as follows: the longitudinal stretching ratio is 5:1, the longitudinal stretching temperature is 90°C, the transverse stretching ratio is 3:1, and the transverse stretching temperature is 90°C; S2: A 5 nm thick transition layer was deposited on each side of the current collector base film using a nickel-chromium alloy target (purity: 99.99%) as the target material by magnetron sputtering (power 4.0 kW, argon gas flow rate 50 mL / min, coating vacuum degree 0.08 Pa, coating time 1 s, main roller temperature during coating process 10°C) to obtain a composite current collector film A; S3: A 900 nm thick metal layer was deposited on both sides of the transition layer of the composite film A using a copper target (purity: 99.99%) as the target material by magnetron sputtering (power of 12.0 kW, argon flow of 70 mL / min, coating vacuum of 0.1 Pa, coating time of 100 s, cooling temperature of the main roller during the coating process of -5 °C) to obtain a composite film B; S4: The composite membrane B is immersed in a 0.5 g / L chromic anhydride aqueous solution at 25°C until the protective layer thickness is 50 nm, then washed in a pure water tank, and dried in an oven at 60°C to obtain a composite current collector with a total thickness of 6.41 μm.

[0039] Comparative Example 3 is based on Example 9, and methacrylamide is directly added to the oil phase; comprising the following steps: S1: 2.5wt% heat-expandable microspheres (average diameter of 10μm) were uniformly mixed with 97.5wt% polypropylene, melted at 300℃ for 30 minutes, extruded, and biaxially stretched to obtain a 4.5μm current collector base film; The process conditions of biaxial stretching are as follows: the longitudinal stretching ratio is 5:1, the longitudinal stretching temperature is 90°C, the transverse stretching ratio is 3:1, and the transverse stretching temperature is 90°C; S2: A 5 nm thick transition layer was deposited on each side of the current collector base film using a nickel-chromium alloy target (purity: 99.99%) as the target material by magnetron sputtering (power 4.0 kW, argon gas flow rate 50 mL / min, coating vacuum degree 0.08 Pa, coating time 1 s, main roller temperature during coating process 10°C) to obtain a composite current collector film A; S3: A 900 nm thick metal layer was deposited on both sides of the transition layer of the composite film A using a copper target (purity: 99.99%) as the target material by magnetron sputtering (power of 12.0 kW, argon flow of 70 mL / min, coating vacuum of 0.1 Pa, coating time of 100 s, cooling temperature of the main roller during the coating process of -5 °C) to obtain a composite film B; S4: The composite membrane B is immersed in a 0.5 g / L chromic anhydride aqueous solution at 25°C until the protective layer thickness is 50 nm, then washed in a pure water tank, and dried in an oven at 60°C to obtain a composite current collector with a total thickness of 6.41 μm.

[0040] Test evaluation: The composite current collectors of the embodiment and the comparative example were tested for high temperature tensile performance and safety performance. The specific test methods are as follows: 1. High temperature tensile strength test of the composite current collectors prepared in the above examples and comparative examples: 1) Tensile strength: The tensile strength of the composite current collector prepared above was tested at 80° C. according to standard GB / T1040.3-2006, as shown in Table 1.

[0041] 2. Prepare a lithium-ion battery based on the above composite current collector and then conduct a safety performance test.

[0042] 1) Battery preparation: For the positive electrode, the positive electrode current collector uses traditional aluminum foil (thickness 13μm), and the positive electrode material uses LiNi 0.6 Mn 0.2 Co 0.2 O 2 (NCM622); for the negative electrode: the negative electrode current collector adopts the composite current collector prepared by the present invention, and the negative electrode material adopts artificial graphite; for the diaphragm, an alumina ceramic coated polyethylene diaphragm (thickness 25 μm) is adopted; for the electrolyte, 1 mol·L -1 LiPF 6 A carbonate solution, wherein the carbonate includes propylene carbonate, ethylene carbonate and ethyl methyl carbonate in a mass ratio of 1:1:1; using the above materials, assembling a lithium-ion battery according to relevant processes; 2) Safety performance test: A puncture test is used to verify the safety performance of the battery, as follows: the battery prepared above is placed in a puncture test device, wherein the diameter of the puncture needle is 3 mm, the puncture speed is 10 mm / s, the sampling interval is 100 ms, and the sampling time is 15 min; if the safety performance is qualified, the battery should not explode, catch fire, or emit smoke. 100 batteries are used as test samples, as shown in Table 1.

[0043]

[0044] Table 1 Conclusion: It can be seen from Table 1 that the tensile strength of the composite current collector and the safety of the battery are affected by the particle size and content of the heat-expandable microspheres and the melting temperature. Comparative Example 1 is based on Example 1, but heat-expandable microspheres are not added, resulting in a decrease in its high-temperature tensile strength and needle puncture pass rate; Comparative Example 2 is based on Example 1, but heat-expandable microspheres are not added, and the PP film is replaced with a PET film, resulting in a decrease in its high-temperature tensile strength and needle puncture pass rate. Comparative Example 3 is based on Example 9, and methacrylamide is directly added to the oil phase, resulting in a decrease in its high-temperature tensile strength and needle puncture pass rate; because the introduction of ferrosoferric oxide can enhance the strength and stability of the microspheres, allowing them to maintain their shape during thermal expansion, and help regulate the battery temperature to prevent overheating; and (5-(pent-4-en-1-yloxy)pyridin-3-yl)boric acid can enhance the stability and structural integrity of the microspheres, which is beneficial to improving battery safety.

[0045] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A composite current collector, characterized in that: The steps include: S1: uniformly mixing the heat-expandable microspheres and the polymer material, melt-extruding, and biaxially stretching to obtain a current collector base film; S2: depositing a transition layer on both sides of the current collector base film to obtain a composite current collector film A; S3: depositing another metal layer on both sides of the transition layer of the composite film A to obtain a composite film B; S4: depositing another protective layer on both sides of the metal layer of the composite film B to obtain a composite current collector.

2. A composite current collector according to claim 1, characterized in that: The current collector base film includes a heat-expandable microsphere content of 0.5wt%~5wt% and a polymer material content of 95wt%~99.5wt%; the particle size of the heat-expandable microsphere is 5μm~20μm; the biaxial stretching includes longitudinal stretching and transverse stretching, and its process conditions are: the longitudinal stretching ratio is (3~6):1, the longitudinal stretching temperature is 80~110℃, the transverse stretching ratio is (2~4):1, and the transverse stretching temperature is 80~110℃.

3. A composite current collector according to claim 1, characterized in that: The metal layer on any side of the current collector base film is one layer or more layers, the thickness of each layer is 50nm~1200nm, and the total thickness of the metal layer on any side of the current collector base film is 500nm~2000nm; the thickness of the protective layer is 20nm~80nm; the thickness of the current collector base film is 1.0μm~10μm; the thickness of the composite current collector is 3~20μm.

4. A composite current collector according to claim 1, characterized in that: The polymer material includes one or more of polyethylene terephthalate, polypropylene, polybutylene terephthalate, polyethylene naphthalate, polyethylene, polypropylene, polyvinyl chloride, polyvinylidene fluoride, polytetrafluoroethylene, polyphenylene sulfide, polyphenylene oxide, polystyrene, and polyimide; The material of the transition layer includes one or more of aluminum oxide, silicon oxide, titanium oxide, nickel, chromium, titanium, nickel-chromium alloy, nickel-chromium-copper alloy, and silicon-aluminum alloy; The material of the metal layer includes one or more of aluminum, copper, gold, silver, nickel, zinc and alloys thereof; The material of the protective layer includes one or more of nickel, chromium, nickel-chromium alloy, nickel-based alloy, copper-based alloy, copper oxide, aluminum oxide, nickel oxide, chromium oxide, cobalt oxide, copper-chromium oxide, graphite, carbon black, carbon nano-quantum dots, carbon nanotubes, carbon nanofibers, graphene and graphene oxide.

5. A composite current collector according to claim 1, characterized in that: The deposition method of the metal layer includes one or more of evaporation, magnetron sputtering, chemical plating, electroplating, and chemical vapor deposition; the deposition method of the protective layer includes one or more of physical vapor deposition, chemical vapor deposition, in-situ forming, and coating.

6. A composite current collector according to claim 5, characterized in that: When the deposition method of the metal layer is electroplating, the electroplating conditions are: the anode is a high-purity metal with a purity of ≥99.9%, the cathode is a titanium plate; the current intensity is 20000A~50000A, and the current density is 5000A / m 2 ~10000A / m 2 ; The copper ion concentration is generally controlled at 65g / L~100g / L, and the H2SO4 concentration is 180g / L~220g / L; When the deposition method of the metal layer is magnetron sputtering, the conditions of the magnetron sputtering are: using high-purity metal as the target material with a purity of ≥99.9%, the target power supply is a DC power supply with a power of 2kW~20kW, the vacuum degree is ≤0.1Pa, the gas source is argon, the argon flow rate is 20mL / min~500mL / min, and the coating time each time is 0.1s~120s.

7. A composite current collector according to claim 1, characterized in that: The preparation method of the heat-expandable microspheres is as follows: (1) polyvinyl pyrrolidone, sodium dodecyl sulfate, modified ferroferric oxide, sodium chloride and deionized water are uniformly mixed to obtain a water phase for standby use; acrylonitrile, methyl methacrylate, methyl acrylate, N,N-dimethylacrylamide, butadiene, trimethylolpropane trimethacrylate, isopentane and dilauroyl peroxide are uniformly mixed to obtain an oil phase for standby use; (2) the pressure is set to 1MPa-1.2MPa, the water phase and the oil phase are mixed at room temperature for 15-20 minutes at a rotation speed of 5000rpm-8000rpm, the temperature is raised to 40°C-60°C, the reaction is carried out for 18-22 hours, the mixture is cooled to room temperature, filtered, washed and dried to obtain the heat-expandable microspheres.

8. A composite current collector according to claim 7, characterized in that: The raw materials of the water phase include the following components: by mass, 80-100 parts of deionized water, 30-40 parts of sodium chloride, 15-20 parts of polyvinyl pyrrolidone, 4-5 parts of sodium dodecyl sulfate, and 5-7 parts of modified ferrosoferric oxide; the raw materials of the oil phase include the following components: by mass, 50-60 parts of methyl acrylate, 30-35 parts of acrylonitrile, 25-35 parts of isopentane, 6-8 parts of methyl methacrylate, 3-5 parts of N,N-dimethylacrylamide, 5-8 parts of butadiene, 3-5 parts of trimethylolpropane trimethacrylate, and 1-3 parts of dilauroyl peroxide.

9. A composite current collector according to claim 7, characterized in that: The preparation method of the modified ferrosoferric oxide is as follows: (1) adding ferric chloride to a mixed solution of propylene glycol and deionized water, uniformly mixing, adding cysteine, reacting at 0.2MPa-0.3MPa and 180°C-210°C for 5-6 hours, cooling to room temperature, washing, and drying to obtain thiolated ferrosoferric oxide; (2) ultrasonically dispersing thiolated ferrosoferric oxide in tetrahydrofuran, adding methacrylamide, (5-(pent-4-en-1-yloxy)pyridin-3-yl)boric acid, and azobisisobutyronitrile, and irradiating the mixture at an emission wavelength of 365nm and a light intensity of 90mW / cm 2 ~100mW / cm 2 Irradiate under ultraviolet light for 2 to 3 hours to obtain modified ferrosoferric oxide.

10. A composite current collector according to claim 9, characterized in that: The raw materials of the thiolated ferrosoferric oxide include the following components: by mass, 0.6-0.8 parts of ferric chloride, 5-10 parts of propylene glycol, 5-10 parts of deionized water, and 1.5-2.2 parts of cysteine; the raw materials of the modified ferrosoferric oxide include the following components: by mass, 0.5-1 parts of thiolated ferrosoferric oxide, 3-4 parts of methacrylamide, 1-2 parts of (5-(pent-4-en-1-yloxy)pyridin-3-yl)boric acid, 0.002-0.0025 parts of azobisisobutyronitrile, and 20-25 parts of tetrahydrofuran.

Citation Information

Cited By

  • Preparation method and application of functional current collector with low thermal shrinkage and high tensile strength

    CN119864424A

  • High-strength PP film for composite current collector and preparation method of high-strength PP film

    CN120118367A

  • A high-strength PP film for composite current collectors and its preparation method

    CN120118367B